2019
DOI: 10.1097/shk.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

3-Factor Versus 4-Factor PCC in Coagulopathy of Trauma: Four is Better Than Three

Abstract: Level III, Therapeutic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 25 publications
1
34
0
2
Order By: Relevance
“…In the past few decades, impressive advances have been made in the understanding of coagulopathy following blunt and penetrating trauma resulting in promising clinical interventions to diagnose, prevent, and treat trauma induced coagulopathy (TIC) ( 1 5 ). While the extent of research in the burn population has lagged in comparison with other types of trauma, a growing body of knowledge elucidates many unique characteristics of BIC.…”
mentioning
confidence: 99%
“…In the past few decades, impressive advances have been made in the understanding of coagulopathy following blunt and penetrating trauma resulting in promising clinical interventions to diagnose, prevent, and treat trauma induced coagulopathy (TIC) ( 1 5 ). While the extent of research in the burn population has lagged in comparison with other types of trauma, a growing body of knowledge elucidates many unique characteristics of BIC.…”
mentioning
confidence: 99%
“…Factor VIIa has been used alone and in combination with PCC3 to compensate for the low amount of factor VII [14,15]. Activated PCC has been used off-label for EWR [54]. Given the differing composition of these products as containing active factor VII and that guidelines do not currently recommend these products for EWR, we chose to not include these products in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing PCC3 to PCC4 outside of the setting of EWR have similar results. Zeeshan et al found faster correction of INR with PCC4 compared to PCC3 in a propensity-score-matched analysis of patients treated for coagulopathy of trauma (PCC4: n = 125, 365 minutes vs. PCC4: n = 125, 428 minutes, p < 0.01), fewer units of FFP transfused (6 units vs. 8 units, p < 0.03) [53]. Also, the incidence of TE and mortality were similar between the PCC groups.…”
Section: Discussionmentioning
confidence: 99%